Astrocytes Are Required for Oligodendrocyte Survival and Maintenance of Myelin Compaction and Integrity - Tognatta, Reshmi; Karl, Molly T.; Fyffe-Maricich, Sharyl L.; Popratiloff, Anastas; Garrison, Eric D.; Schenck, Jessica K.; Abu-Rub, Mohammad; Miller, Robert H. (Frontiers in Cellular Neuroscience, 2020)
Astrocytes have been implicated in regulating oligodendrocyte development and myelination in vitro, although their functions in vivo remain less well defined. Using a novel approach to locally ablate GFAP+ astrocytes, we demonstrate that astrocytes are required for normal CNS myelin compaction during development, and for maintaining myelin integrity in the adult. Transient ablation of GFAP+ astrocytes in the mouse spinal cord during the first postnatal week reduced the numbers of mature oligodendrocytes and inhibited myelin formation, while prolonged ablation resulted in myelin that lacked compaction and structural integrity. Ablation of GFAP+ astrocytes in the adult spinal cord resulted in the rapid, local loss of myelin integrity and regional demyelination. The loss of myelin integrity induced by astrocyte ablation was greatly reduced by NMDA receptor antagonists, both in vitro and in vivo, suggesting that myelin stability was affected by elevation of local glutamate levels that were elevated in vitro following astrocyte ablation. Furthermore, targeted delivery of glutamate into adult spinal cord white matter resulted in reduction of myelin basic protein expression and localized disruption of myelin compaction which was also reduced by NMDA receptor blockade. The pathology induced by localized astrocyte loss and elevated exogenous glutamate, supports the concept that astrocytes are critical for maintenance of myelin integrity in the adult CNS and may be primary targets in the initiation of demyelinating diseases of the CNS, such as Neuromyelitis Optica (NMO).